PENGARUH BACK MASSAGE TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI: LITERATURE REVIEW - Fitri Yulita, Rita (JURNAL KESEHATAN KARTIKA, 2021)
According to the World Health Organization (2019) hypertension is the cause of premature death throughout the world. Increased blood pressure that lasts for a long time (persistent) can cause a damage to kidneys (renal failure), heart (coronary heart disease), and brain (stroke). One of the efforts to prevent this is by performing back massage therapy, which can vasodilate blood vessels and increase the reflex baroreceptor response so that it affects the decrease in sympathetic nervous system activity and increases the activity of the parasympathetic nervous system. The purpose of this literature review is to identify the effect of back massage on blood pressure in hypertensive patients. This research method uses a literature review with a systematic literature review approach. This research was conducted using online search methods through several search engines including Google Scholar, Garuda, Science Direct, EBSCO, and PubMed using the keywords "back massage" and "hypertension". The analysis method uses PICO. The results of the literature review of 5 articles show the effect of back massage on blood pressure in clients with hypertension, where there is a decrease in systolic and diastolic blood pressure after being given back massage intervention. The results of this literature review are expected to add information and become a source of reference in an effort to prevent and overcome hypertension, such as checking blood pressure regularly and trying to lower and keep blood pressure within normal limits, one of which is by regularly performing back massage actions.